Product versus Process: Innovation Strategies of Multi-Product Firms - Lisandra Flach; Michael Irlacher (Center for Economic Studies and ifo Institute (CESifo), 2015)
We investigate the effect of better access to foreign markets on innovation strategies of multi-product firms in industries with different scope for product differentiation. Industry-specific demand and cost linkages induce a distinction between the returns to innovation. In differentiated industries, cannibalization is lower and firms invest more in product innovation. In homogeneous industries, firms internalize intra-firm spillovers and invest more in process innovation. We test these predictions using Brazilian firm-level data. Following an exchange rate devaluation, firms have better access to foreign markets and exploit economies of scale in innovation. We evaluate the differential effects across industries and show that the type of innovation depends on the degree of product differentiation.
Keywords: F12; F14; L25; 330; multi-product firms; innovation; product differentiation; cannibalization effect; spillovers; market size effect